PENGUKURAN SISTEM INFORMASI E-LEARNING POLIJE MENGGUNAKAN STANDAR ISO 9126 - Ageng Puji Pangestu; Agitha Rizky Aldiansyah; Ivan Mahdavikia; Rizki Makhfud Nur’ atsani; Annisah Nabilah (Jurnal Teknologi Informasi dan Komunikasi, 2023)
Technological sophistication forces the world of education to use E-Learning. E-Learning at Jember State Polytechnic makes things easier for students, for example attendance, collecting assignments, assignment calendars and various others. However, when using E-Learning, there will definitely be system problems or what are called bugs. This study tests the Jember State Polytechnic E-Learning function to collect problem identification data. The aim is to measure the quality of the platform with the ISO 9126 standard. From the research results, Jember State Polytechnic E-Learning achieved a quality score of 98.4%, "Very Good" according to the ISO/IEC 9126 standard. Suitable for use and optimal in online learning.